Vineyard weed control using alternative methods compared to glyphosate-based herbicide - Andrej PAUŠIČ; Mario LEŠNIK; Nuša TURK (Acta Agriculturae Slovenica)
In a two-year field experiment, six different weed control methods were studied. The methods were: use of the herbicide glyphosate (GL), use of herbicides based on acetic acid (AA), pelargonic acid (PA) and citrus essential oil (EO), mowing weeds with a thread trimmer (TT) and flaming of weeds with fire (FL). Alternative methods of weed control were significantly less effective than the use of herbicide glyphosate. Due to the lower efficiency of alternative methods, large yield losses have occurred, on average, 31 % at AA, 30.6 % at PA, 22.7 % at EO, 5.4 % at TT and 12.9 % at FL in two years. The cost of carrying out controls with alternative methods was significantly higher than the cost of GL. AA it was higher by 3.2-times, in PA by 7.1-times, in EO by 3.8-times, in TT by 3.8- times and in FL by 5.8-times on average in two years. To achieve a comparable control efficiency of GL, five applications of alternative preparations per year have to be performed, or four times mowing of weeds or five weed flaming operations per year.